Epistemology and its implications in designing the cover of Popular Heritage magazine (Al-Academy, 2024)
Epistemology is real and deserves follow-up and attention for its logical and objective role in what it provides to humanity in order to provide the correct information due to its accuracy and solidity in showing and sorting a common cognitive reality that helps in explaining the correspondence between our subjective thoughts and the natural external world to determine the meanings of shapes, through the effort and performance provided by the designer to reflect On the cover of the magazine, the research problem was revealed in the following question: How was epistemology reflected in the design of the covers of Popular Heritage magazine? While the aim of the research was set to identify (epistemology) and its reflection in the design of the covers of Popular Heritage magazine, the theoretical framework included in the first section (the intellectual concepts of epistemology), while the second section was (the structural components of the magazine cover), and in the third chapter (3) samples were described and analysed. Research, as for presenting the results and conclusions: -Epistemology begins with a tool of feeling whose reference is knowledge that does not describe an internal structure, but rather is based on concepts and meanings that can be tested according to contexts and cognitive systems that result in results that affect aspects of human behavior that can be proven or invalidated. -Epistemology is achieved by adapting the magazine cover designs to the recipient’s considerations and performance preferences, which is based on assembling images and shapes in a deliberative manner that stimulates the recipient’s cognitive awareness and increases the rate of interaction with the content of the magazine